A STUDY OF COMPLAINT TRENDS AND STRATEGIC IMPROVEMENTS: A FOUR-YEAR ANALYSIS OF SIX MALAYSIAN MUNICIPALITIES - Salleh, Nor Aini; Alauddin, Kartina; Abdul Talib, Yuhainis; Ismail, Kharizam (PLANNING MALAYSIA, 2024)
The primary aim of the study is to analyse the pattern of complaints received by the COB related to strata living across six municipalities categorised under category 2 over a four-year period. Additionally, the study examines the municipality with the highest number of complaints over four years, aiming to propose effective strategies, such as enhancing a clear understanding of SMA Act 2013 communication channels and enhanced dispute resolution mechanisms, to reduce complaint rates. By utilising a desk study analysis approach, the research emphasises the importance of clear legal provisions, policies, and guidelines, recognising the human factor's influence. The analysis spans 2016 to 2019, focusing on six municipalities under category 2. The study employs descriptive analysis and graphical representation to illustrate complaint trends over the specified years. This research provides insights into the patterns of complaints across municipalities and categories, offering valuable information for targeted improvements and strategic planning.